2010
DOI: 10.1111/j.1365-294x.2010.04968.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and differentiation of Rivulus hartii across Trinidad and neighboring islands

Abstract: Diversification of freshwater fishes on islands is considered unlikely because the traits that enable successful colonization-specifically, broad salinity tolerances and the potential for oceanic dispersal-may also constrain post-colonization genetic differentiation. Some secondary freshwater fish, however, exhibit pronounced genetic differentiation and geographic structure on islands, whereas others do not. It is unclear what conditions give rise to contrasting patterns of differentiation because few comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 76 publications
(213 reference statements)
0
20
0
Order By: Relevance
“…Though an accurate review of the fish fauna of Tobago is hampered by the fact that there have been few reported surveys on the island (limited to Ramnarine et al 1994 andPhillip 1998), recent phylogenetic evidence from Anablepsoides hartii (Walter et al 2011) has shown that the zoogeography of Tobago may be more complex than previously expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though an accurate review of the fish fauna of Tobago is hampered by the fact that there have been few reported surveys on the island (limited to Ramnarine et al 1994 andPhillip 1998), recent phylogenetic evidence from Anablepsoides hartii (Walter et al 2011) has shown that the zoogeography of Tobago may be more complex than previously expected.…”
Section: Discussionmentioning
confidence: 99%
“…Although we here refer to all Rivulus (=Anablepsoides) from Trinidad as A. hartii, recent genetic work (Walter et al 2011) indicates that differentiation has occurred, some of which warrants taxonomic recognition.…”
Section: Poecilia Vivipara Bloch and Schneider 1801 [Swamp Guppy Swampmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent study reveals the presence of different genetic lineages of R. hartii in Trinidad [45]. The geographic boundaries of these lineages are poorly understood, but some appear to be defined by stream or watershed boundaries [45].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study reveals the presence of different genetic lineages of R. hartii in Trinidad [45]. The geographic boundaries of these lineages are poorly understood, but some appear to be defined by stream or watershed boundaries [45]. A phylogenetic signature in organismal stoichiometry has been observed even within closely related insect taxa [46], and it is possible that combining phylogenetic and stoichiometric analyses can explain the remaining portion of spatial variability in the stoichiometry of R. hartii .…”
Section: Discussionmentioning
confidence: 99%